2019
DOI: 10.3390/f10100852
|View full text |Cite
|
Sign up to set email alerts
|

Direct Method of Measuring the pH Value of Wood

Abstract: A direct method of measuring the pH value of wood substance is proposed in the paper. The achieved results were completed by determining the pH value on the wood surface using the contact method. Moreover, the results were compared to the results achieved using the indirect methods to determine the pH value in cold water, as well as hot water, extract of wood. Using the direct method for measuring the pH value in drilled fresh sawdust, the pH value of beech was 5.11, of birch was 5.29, of alder was 4.88, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 3 publications
(4 reference statements)
4
30
0
Order By: Relevance
“…Effect of acidic pH on fluorescence properties of fluorescent protein mCherry of S. aureus was studied at pH of 3.5, 4 and 6. These values were chosen because the ground wood samples of oak, Douglas fir and poplar had pH values of 3.8, 4.4, 6.4, respectively 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of acidic pH on fluorescence properties of fluorescent protein mCherry of S. aureus was studied at pH of 3.5, 4 and 6. These values were chosen because the ground wood samples of oak, Douglas fir and poplar had pH values of 3.8, 4.4, 6.4, respectively 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, mCherry S. aureus was chosen in the present work to investigate red S. aureus bio-distribution on green wood and melamine surfaces. A critical point was the high acidic environment of wood 21 , for example, the pH of oak wood is 3.5, which could influence the investigation. However, we have demonstrated that strong acidic pH responsible for green fluorescence switch of mCherry could be avoided by using phosphate buffer for bacterial inoculation and the storage of inoculated wood.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was drilled using an electric drill machine, and the resulting sawdust was pressed back into the opening; subsequently, a piercing electrode was applied. After achieving appropriate contact between the sawdust and probe, changes in the pH value were recorded every 15 s for a 7-min period [16].…”
Section: Methodsmentioning
confidence: 99%
“… Nemli, Yıldız & Gezer (2008) stated that a lower pH in lignocellulosic materials may be attributed to presence of more amounts of extractives and resin acids. The acidic reaction of most tree species is caused by free acids and acidic groups easy to be separated, that is, especially by acetic acid and acetyl groups ( Geffert, Geffertova & Dudiak, 2019 ). Variations of pH along the stem have also been associated with the presence of extractives ( Campbell, Kim & Koch, 1990 ).…”
Section: Discussionmentioning
confidence: 99%